Rectal stump mucocele after a Hartmann's procedure causing mechanical ileus. Issue 1 (8th January 2021) - Longchamp, Gregoire; Colucci, Nicola; Ris, Frederic; Buchs, Nicolas C
Abstract : Two years after a Hartmann's procedure, an 85-year-old woman was admitted at our emergency department with abdominal bloating and severe constipation for 5 days. Abdominal CT showed a large rectal stump mucocele associated with compression of surrounding structures, causing a mechanical ileus and a bilateral pyelocaliceal dilatation. Successful transanal drainage with a rectal catheter allowed rapid recovery.